Dinamika Sosial Pasca Pengaturan Delik Penghinaan Terhadap Presiden dalam Undang-Undang No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana di Indonesia - Yelena Fitria Mahadewi; Zulfan (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2026)
The re-regulation of the criminal offense of insulting the President and Vice President in Articles 218-220 of the Criminal Code (KUHP) has sparked debate regarding the boundaries between criticism and insult, as well as the state's role in regulating public expression. This phenomenon is further complicated by the development of open and participatory communication in the digital era. From a sociological perspective, the existence of a legal norm is understood not only as a formal regulatory instrument but also as a factor influencing legal awareness and social behavior. This study aims to analyze the social dynamics and public response to the provisions of the article on insulting the President in the new Criminal Code, particularly in relation to changes in norms of expression. The method used is a qualitative descriptive-analytical approach, through data collection in the form of in-depth interviews, public discourse analysis, sociological studies of changing practices and norms in society, and supported by previous literature studies. This study utilizes criminality theory, social control theory, and the concept of a democratic rule of law as analytical tools. The findings of this study confirm that law not only functions as a tool of social control but also shapes the construction of norms and collective awareness regarding the limits of expression in society. Therefore, understanding social responses is crucial for assessing the effectiveness and legitimacy of legal policies in practice.